Intensity and volumetric characterizations of hydraulically driven fractures by hydro-mechanical simulations. (March 2017) - Papachristos, E.; Scholtès, L.; Donzé, F.V.; Chareyre, B.
Abstract: A fully coupled hydro-mechanical model based on the discrete element method has been built up to characterize the properties of fluid driven fractures. The rock mass is represented by a set of discrete elements interacting through elastic-brittle bonds that can break to form cracks which can coalesce to form fractures. The fluid flow between the elements is computed as a function of the dual pore space deformation in the intact medium and of the cracks' aperture in the fractures through a finite volume scheme. A series of hydraulic fracturing simulations were performed on intact specimens subjected to different loading conditions. The respective contributions of the matrix permeability, fluid compressibility, injection flow rate and state of stress are investigated while the effect of the distance between the perforation clusters, the wellbore-deviation from the minimum principal stress direction and the orientation of the injection slots for multiple injection treatments along a wellbore segment. For the analysis the evolutions of the P 33 (fracture volume) and P 32 (fracture intensity) indices are followed. The results show how, for a single injection treatment, P 33 and P 32 values can be affected by the state of stress inside the medium. Also, they show that aligning the perforation slots with the maximum horizontal stress direction might be a straightforward solution to optimize the opening of the induced fractures. Abstract : Highlights: We study propagation of hydraulically driven fractures depending on the fluid and rock properties as well as by the hydraulic and stress loading conditions. We have developed a 3D fully coupled hydro-mechanical model based on the discrete element method to characterize the properties of these fluid driven fractures. The respective contributions of the matrix permeability, fluid compressibility, injection flow rate and state of stress have been investigated. The results show how, for a single injection treatment, P33 and P32 values can be affected by the state of stress inside the medium. They also show that the possibility of aligning the perforation slots with the maximum horizontal stress direction might be a straightforward solution to optimize the opening of the induced fractures.